PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PELANGGAN DALAM PEMBELIAN MOBIL BEKAS DI SHOWROOM AGUNG JAYA MOTOR KOTA LUBUKLINGGAU - Ronal Aprianto; Rudi Azhar; Renita Puspa Sari (Jurnal Media Ekonomi (JURMEK), 2018)
This study with the results of preliminary observations can be seen that the identification of problems in this study are related to promotion, price and purchasing decisions of used cars, the title of this study is the influence of promotion and price on the decision to buy used cars in Agung Jaya Motor Showroom Lubuklinggau City, with 3 formulation of the problem of whether there is a promotion and price influence on the used car purchase decision, is there any influence of promotion on the used car purchase decision, and whether there is a price effect on the used car purchase decision. The method used is quantitative, with the technique of collecting observation data, documentation and questionnaires. Respondents in this research are 74 customers. The results showed that there were promotional effects on customer decisions in purchasing used cars in the Agung Jaya Motor Showroom in Lubuklinggau City, there were price effects on customer decisions in buying used cars in the Agung Jaya Motor Showroom in Lubuklinggau City, and there were promotional and price influences on customer decisions in purchase of used cars at the Agung Jaya Motor Showroom in Lubuklinggau city.